LEGAL PROTECTION OF OIL AND GAS MINING TO REALIZE SUSTAINABLE DEVELOPMENT - Santoso, Ribuddi; Athoriq, Muhammad A; Fairuz, Numara Ardelia; Putri, Ananda M Janur (Communale Journal, 2023)
Indonesia, as one of the countries with abundant natural resource potential, such as oil and gas, plays an essential role in the global energy landscape. As a Mining Authority (KP) stakeholder who collaborates with contractors through the oil and gas mining contract system, the government contributes to using oil and gas in various sectors, especially the industrial sector, as part of sustainable development efforts. Sustainable development with an environmental perspective is a conscious and planned effort that incorporates ecological aspects, including natural resources, into the development process to ensure the ability, well-being, and quality of life of current and future generations. The components of sustainable development include social, economic, and environmental aspects. The paradigm of sustainable economic development aims to achieve optimal production, improve the welfare of economic actors, and preserve the environment. In this paper, we will discuss the regulation of laws and technology for the management and utilization of oil and gas. Oil and gas resources in Indonesia require careful management and prioritization of the principles of sustainable development. The role of government through mining contracts and technological advances contributes to the optimization of oil and gas production. By integrating environmental considerations through technology into the development process and encouraging sustainable practices, Indonesia can ensure long-term resource availability, promote economic growth, and safeguard the well-being of current and future generations.